Job Guarantee: a Structuralist Perspective - Antoine Godin (Revue de la Régulation)
This paper aims at formalising and assessing the validity of the critiques of the Job Guarantee (JG) policy proposed by Minsky (1965). In order to do so, we develop a multisectoral Post-Keynesian Stock-Flow Consistent (PK-SFC) model. Our paper is a step, following Missaglia (2011), towards the creation of a structuralist/ SFC model. We introduce several new features in an PK-SFC model: (i) a more disaggregated households sector than usual, (ii) three production sectors and the possibility of constrained output, and (iii) a more elaborated labor market with endogenous labor supply. We use the model to compare and contrast two Keynesian policies: theJG and a traditional Keynesian Demand Spur (KDS).